Functional state estimation of 14-16 year-old girls, specializeing in race walking - Tuisheva, V. S. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. The training process organization is connected with several important problems solution: physical loads adequacy to individual abilities of an organism, the necessity of their rational regulation according to orientation, volume and power of influence. Functional state of a sportsman is determined by functional and morphological adaptation of the systems of an organism. One of the objective criteria of functional readiness is presented by physical working capacity indices. The speed of adaptive transformations in the organism of sportsmen, their orientation and the achieved level of adaptation are conditioned by the character, volume and orientation of the used loads. Material. The article is about the possibilities of the functional state and female athletes` rehabilitation estimation with the help of "Firstbeat" methodology at a training stage of a thorough sports specialization during the preparatory period. The problem is urgent nowadays, as great importance in race walking has a rational planning of the training loads orientation and its correspondence to specific demands of an effective competitive activity. Research methods: scientific literature analysis and summarizing, monitoring according to "Firstbeat" methodology, testing, methods of mathematical statistics. Result. Anthropometric results (height, weight) of 14-16 year-old female athletes, the research results of average daily average-group ratio of stress reactions and rehabilitation of female athletes are received. According to the research results of the monitoring according to "Firstbeat" methodology, the training lessons of the preparatory period among 14-16 year-old female athletes, specializing in race walking, had a developing training effect, and it gives an opportunity to train the organism of athletes for a tense training activity and further intensive micro cycle. Conclusion. Given in the article research results are interesting for the trainers and the specialists in the sphere of track-and-field athletics.